2020
DOI: 10.1002/cncr.33219
|View full text |Cite
|
Sign up to set email alerts
|

“This is some mess right here”: Exploring interactions between Black sexual minority women and health care providers for breast cancer screening and care

Abstract: BACKGROUND: Few studies have explored how the intersection of race and sexual identity contribute to breast cancer disparities for Black sexual minority women (SMW). Issues within patient-provider relationships, including bias, contribute to health disparities for minority groups. The authors used constructs from self-determination theory (SDT) to explore the nature of health care provider interactions in breast cancer screening and care among Black SMW. METHODS: Participants were sampled nationally through so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
(69 reference statements)
0
20
0
Order By: Relevance
“…Sexual minority women have a lower prevalence of screening mammograms in comparison with heterosexual women for several reasons, including their perceptions of heterosexism and homophobia among providers 22 . In a study of breast cancer screening of Black sexual minority women, Greene et al 23 found that those who had negative experiences with their providers reported that they had in fact made assumptions about them and failed to create supportive and welcoming environments, and this resulted in feelings of alienation among those seeking care. The reality is that there is significant bias on behalf of providers.…”
Section: Discrimination Against Sexual Minority Women In Health Care Settingsmentioning
confidence: 99%
“…Sexual minority women have a lower prevalence of screening mammograms in comparison with heterosexual women for several reasons, including their perceptions of heterosexism and homophobia among providers 22 . In a study of breast cancer screening of Black sexual minority women, Greene et al 23 found that those who had negative experiences with their providers reported that they had in fact made assumptions about them and failed to create supportive and welcoming environments, and this resulted in feelings of alienation among those seeking care. The reality is that there is significant bias on behalf of providers.…”
Section: Discrimination Against Sexual Minority Women In Health Care Settingsmentioning
confidence: 99%
“…In addition to interactions with providers, sexual minorities may be discriminated against by the HCS itself. For example, from our team's previous qualitative work with Black SM women one breast cancer patient expressed frustration that there was a breast cancer support group specifically geared toward male but not female partners of breast cancer survivors 40 . Altogether, these results and examples suggest an increased need for interventions at the provider and healthcare system levels in cancer screening and care to regain trust among racial and SM patients.…”
Section: Discussionmentioning
confidence: 99%
“…1). In a recent qualitative study with BSMW breast cancer care survivors, Greene et al 44 identified several strategies that health care providers could use to improve engagement, including creating a relatable atmosphere that supports the autonomy and self‐efficacy of the person seeking care.…”
Section: Discussionmentioning
confidence: 99%